Detection mode of childhood acute lymphoblastic leukaemia relapse and its effect on survival: a Nordic population‐based cohort study. (27th May 2021) - Jensen, Karen S.; Oskarsson, Trausti; Lähteenmäki, Päivi M.; Flaegstad, Trond; Schmiegelow, Kjeld; Vedsted, Peter; Albertsen, Birgitte K.; Schrøder, Henrik; ,
Summary: Relapse constitutes the greatest threat to event‐free survival after completion of treatment for childhood acute lymphoblastic leukaemia (ALL). However, evidence on optimal follow‐up schedules is limited. The aims of the present population‐based cohort study were to assess the value of current follow‐up schedules after completion of Nordic Society of Paediatric Haematology and Oncology ALL protocol treatment and to estimate the impact of relapse detection mode on overall survival (OS). Among 3262 patients diagnosed between 1992 and 2014 and who completed treatment, 338 developed a relapse. Relapse detection was equally distributed between extra visits (50·8%) and scheduled follow‐up visits (49·2%). All cases detected at an extra visit and 64·3% of cases detected at a scheduled visit presented with symptoms or objective findings. Neither the mode of detection {adjusted hazard ratio 0·95, [95% confidence interval (CI) 0·61–1·48] for scheduled visits} nor the duration of symptoms was an independent risk factor for OS after relapse. The estimated number of scheduled blood samples needed to diagnose one subclinical relapse during the first 5 years after treatment cessation was 1269 (95% CI 902–1637). In conclusion, based on OS data, scheduled visits after cessation of therapy seem to yield no extra benefit. These results should frame future follow‐up strategies.